The Influence of Digital Marketing on Purchasing Decisions at Tanah Abang Market - Maolana, Rifky; Andini, Chantika Trie; Mukaromah, Mukaromah; Juliansyah, Siti Nur (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to analyze the influence of digital marketing on consumer purchasing decisions using a case study of Tanah Abang Market. The primary focus of the study is brand perception, digital marketing strategies, and how digitalization affects the loyalty and competitiveness of businesses in traditional markets that are now adapting to technology. This study uses a qualitative approach, emphasizing the subjective meanings and experiences of consumers and businesses. The analysis process was conducted inductively using case study, phenomenology, and ethnography techniques to gain an in-depth understanding of digital marketing strategies, including the use of social media, digital content optimization, and consumer purchasing experiences. The results show that digital marketing contributes significantly to increased purchasing decisions, particularly through factors such as ease of access to information, brand trust, and the effectiveness of digital-based promotions. Thus, digitalization has proven to be a key factor in increasing consumer loyalty and strengthening the position of traditional markets in the modern era.